2021
DOI: 10.3390/app11020662
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Liquid Phase Polymerization of HEMA by Atmospheric-Pressure Plasma Discharges for Ti Dental Implants

Abstract: Dental implants can fail due to various factors, in which bad tissue integration is believed to have a significant role. Specific properties of the implant surface, such as its chemistry and roughness, are of paramount importance to address specific cell responses, such as the adsorption of proteins, as well as the adhesion and differentiation of cells, which are suitable for biomaterial and tissue engineering. In this study, an acrylate-containing coating was produced on titanium surfaces through the atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…The obtained hydrophilic coatings decreased Staphylococcus aureus and Escherichia coli adhesion. These surfaces were produced for dental implant antiadhesive effectiveness (Buxadera-Palomero et al 2021).…”
Section: Cold Plasma Treatments Of Materials For Preventing Bacterial Adhesionmentioning
confidence: 99%
“…The obtained hydrophilic coatings decreased Staphylococcus aureus and Escherichia coli adhesion. These surfaces were produced for dental implant antiadhesive effectiveness (Buxadera-Palomero et al 2021).…”
Section: Cold Plasma Treatments Of Materials For Preventing Bacterial Adhesionmentioning
confidence: 99%
“…Currently, functional polymers and are experiencing a rapid and continuous progress as drug delivery and protein purification systems. Due to their diversity, surface and bulk properties, polymers are the most effective biomaterials applied in drug formulations and in drug delivery devices such as implants [133][134][135]. Recent drug delivery systems involve dendrimers, micelles, polymeric nanoparticles, liposomes, microcapsules, cell ghosts, and lipoproteins.…”
Section: Advances In Biomedical Applicationsmentioning
confidence: 99%
“…Buxadera and co-workers reported that the atmospheric pressure plasma jet polymerization of a liquid precursor, 2-hydroxyethyl methacrylate, on titanium yielded a coating with enhanced fibroblast adhesion and simultaneously decreased Staphylococcus aureus and Escherichia coli adhesion, which could be relevant for dental implants [1]. A different strategy was employed by Sardella et al, who compared plasma enhanced-chemical vapor deposition (PE-CVD) of polyethylene oxide (PEO)-like coatings generated either at low pressure and also aerosol-assisted atmospheric pressure PE-CVD.…”
Section: Surface Functionalization and Coating Of Biomedical Materialsmentioning
confidence: 99%